Description Of The Compliance Of Pregnant Women In Consuming Fe Tablets At Puskesmas Kumbe City Of Bima, 2023 - Yati Purnama; Eti Noviatul Hikmah (Jurnal EduHealth, 2023)
Programs to prevent anemia in pregnant women by providing iron (Fe) supplements but the results have not been very satisfactory, as seen from the prevalence rate which is still high. According to WHO (2019) the prevalence of anemia in pregnant women in Indonesia is 41.8%. The results of the 2018 Indonesian Basic Health Research showed that 48.9% of pregnant women in Indonesia experienced anemia and this percentage had increased compared to the 2013 Riskesdas data, which was 37.1%. Data from the NTB Health Office shows the number of pregnant women suffering from anemia has increased between 2019 and 2020. In 2019 there were 9% of pregnant women in NTB who had anemia, increasing to 10.88% ( The purpose of this study is to find out the description of pregnant women's compliance in consuming Fe tablets at the Kumbe Health Center in 2023. This type of research is research quantitative descriptiveby design Cross Sectional. The population is pregnant women at the Kumbe Health Center in 2023 504 people with a sample of 50 people used the technique accidental sampling. Data analysis used univariate analysis by calculating the frequency distribution. The results of this study indicate that the adherence of mothers in consuming Fe tablets at the Kumbe Health Center in 2023 is mostly in the obedient category, namely 30 people (60%). And those who did not comply were 20 people (40%), Compliance of Pregnant Women consuming Fe Tablets based on the level of knowledge at the Kumbe Health Center, Disobeying consuming Fe tablets with sufficient knowledge, namely 20 people (40%), Compliance of Pregnant Women consuming Fe Tablets based on motivation at Most of the compliant pregnant women consuming Fe tablets with high motivation were 20 people (40%), the adherence of pregnant women consuming Fe tablets was based on family support at the Kumbe Health Center that most of the obedient pregnant women consumed Fe tablets with family support 25 respondents (50%) Compliance with pregnant women consuming Fe tablets based on the frequency of ANC visits at the Kumbe Health Center with good ANC visits frequency of 20 pregnant women (40%), Compliance with pregnant women consuming Fe tablets based on slight side effects of 20 respondents (40 %),